Pengaruh Social Media Marketing, E-Word of Mouth dan Citra Merek Terhadap Keputusan Pembelian di Habaka Thrift Shop (Survei pada Generasi Z di Surakarta) - Garned Sulton Ariesta; Sumaryanto Sumaryanto (Indo Publishing, 2026)
This study aims to analyse the influence of social media marketing, e-word of mouth, and brand image on purchasing decisions at the Habaka business unit. Using a quantitative approach with primary data sources, data collection was carried out by distributing questionnaires to 100 respondents. The sample was selected using purposive sampling with specific criteria, namely Generation Z in Surakarta who have knowledge of Habaka ThriftShop’s social media. The collected data was then processed using a series of statistical analysis methods, including descriptive analysis, multiple linear regression, t-tests, F-tests to assess model fit, and analysis of the coefficient of determination (R²). Partial testing via t-tests revealed that all three independent variables made a significant contribution to consumer behaviour. The social media marketing variable was found to have a significant influence on purchasing decisions, with a p-value of 0.000 (p < 0.05). Similar findings were obtained for the e-word-of-mouth and brand image variables, which each demonstrated a significant influence on purchasing decisions at Habaka, with p-values of 0.003 and 0.000 respectively. Overall, the results of this study confirm that digital marketing strategies, electronic consumer-to-consumer communication, and brand perception are key determinants in influencing purchasing decisions among Generation Z.